The Ancient Chinese Decoction Yu-Ping-Feng Suppresses Orthotopic Lewis Lung Cancer Tumor Growth Through Increasing M1 Macrophage Polarization and CD4+ T Cell Cytotoxicity - Wang, Lixin; Wu, Wenbin; Zhu, Xiaowen; Ng, Wanyi; Gong, Chenyuan; Yao, Chao; Ni, Zhongya; Yan, Xuewei; Fang, Cheng; Zhu, Shiguo (Frontiers in Pharmacology, 2019)
Background: The tumor microenvironment (TME) has a deep influence on cancer progression and has become into a new target for cancer treatment. In our previous study, we found that Yu-Ping-Feng (YPF), an ancient Chinese herbal decoction, significantly inhibited the Lewis lung cancer (LLC) tumor growth in a subcutaneous xenograft tumor model, and prolonged the survival of tumor-bearing mice. But the regulation of Yu-Ping-Feng on tumor microenvironment is unknown. Methods: To access the effect of Yu-Ping-Feng on non-small cell lung cancer, an orthotopic luciferase stably expressed Lewis lung cancer tumor model was established on C57BL/6 mice, and then the survival and the tumor growth were evaluated. To address the tumor microenvironment immune regulation, the percentages of CD4+ T cells, CD8+ T cells, natural killer cells (NK), regulatory T cells (Treg), macrophages, and myeloid-derived suppressor cells (MDSC) in spleens and tumor tissues, the macrophage polarization and CD4+ T cell cytotocixity were analyzed by flow cytometry, biophotonic cell killing activity assay, real-time PCR and western-blot. Results: Yu-Ping-Feng significantly prolonged orthotopic lung tumor-bearing mouse survival, and increased the percentages of CD4+ T cell and M1 macrophages and the cytotoxicity of CD4+ T cells. Yu-Ping-Feng significantly enhanced macrophage-mediated lysis of LLC in a concentration-dependent manner, and had no effect on CD4+ T cell-mediated lysis of LLC, but significantly increased CD4+ T cell-mediated lysis after co-incubated with macrophages. In addition, Yu-Ping-Feng induced M1 macrophage polarization through promoting the phosphorylation of STAT1. Conclusion: Yu-Ping-Feng induced M1 macrophages polarization, and then activated CD4+ T lymphocytes, resulting in killing of LLC cells. Yu-Ping-Feng was a potent regulator of M1 macrophage polarization and might have a promising application in tumor immunotherapy.